Pengaruh Return on Equity dan Current Ratio Terhadap Price to Book Value Dengan Debt to Equity Ratio Sebagai Variabel Intervening Pada Perusahaan Transportasi di Bursa Efek Indonesia 2015-2018 - Khana Saputri; Widya Astuty; Muis Fauzi Rambe (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
The purpose of this study was to determine the effect of Return on Equity and Current Ratio on Price to Book Value with Debt to Equity Ratio as an intervening variable in transportation companies on the Indonesia Stock Exchange. The partial test results with is that return on equity has a significant effect on the debt to equity ratio the current ratio has no significant effect on debt to equity ratio. The second equation shows that return on equity has a significant effect on price to book value, current ratio has a significant effect on price to book value and debt to equity has a significant effect on price to book value. The second equation proves that return on equity, current ratio and debt to equity ratio have a significant effect on price to book. The test using path analysis proves that the debt to equity ratio can be an intervening variable between the variable return on equity to price to book value and the debt to equity ratio can not be an intervening variable between the variable current ratio to price to book value.